2017
DOI: 10.1039/c7ra07551k
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical properties of metal nanoparticles: a review

Abstract: Metal nanoparticles (MNPs) hold great technological promise because of the possibility of engineering their electronic and optical properties through material design. One of the effective methods to fabricate MNPs is ion implantation. In this review, recent results on the nonlinear optical properties of nanoparticles (including copper, silver, gold, and bismuth nanoparticles) doped in various bases have been discussed. Some specific optical nonlinear properties, such as nonlinear refraction, two-photon absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
121
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(124 citation statements)
references
References 104 publications
2
121
0
1
Order By: Relevance
“…[2,3,20,21] High β values in MNPs are desirable for applications such as frequency conversion, switching and optical modulation. [22] Studies on 13-nm gold particles have shown very high β values of 3000 × 10 À 30 esu per atom at an excitation wavelength of 820 nm, similar to that of the best molecular chromophores, which was attributed to effective resonance enhancement near the nanoparticle LSPR. [12] It was first observed by Vance et al [12] that β is highly sensitive to AuNP aggregation induced by increasing NaCl concentration and that HRS is at least an order of magnitude more sensitive at picking up aggregation in comparison to Rayleigh scattering (RS), showing that HRS is useful for biosensing assays.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[2,3,20,21] High β values in MNPs are desirable for applications such as frequency conversion, switching and optical modulation. [22] Studies on 13-nm gold particles have shown very high β values of 3000 × 10 À 30 esu per atom at an excitation wavelength of 820 nm, similar to that of the best molecular chromophores, which was attributed to effective resonance enhancement near the nanoparticle LSPR. [12] It was first observed by Vance et al [12] that β is highly sensitive to AuNP aggregation induced by increasing NaCl concentration and that HRS is at least an order of magnitude more sensitive at picking up aggregation in comparison to Rayleigh scattering (RS), showing that HRS is useful for biosensing assays.…”
Section: Introductionmentioning
confidence: 96%
“…However, spherical MNPs exhibit frequency doubling in solution, which is attributed to local imperfections and field enhancements at the particle surface as well as retardation effects . High β values in MNPs are desirable for applications such as frequency conversion, switching and optical modulation . Studies on 13‐nm gold particles have shown very high β values of 3000×10 −30 esu per atom at an excitation wavelength of 820 nm, similar to that of the best molecular chromophores, which was attributed to effective resonance enhancement near the nanoparticle LSPR …”
Section: Introductionmentioning
confidence: 99%
“…High surface‐to‐volume ratio coupled with ease of surface functionalization leads to nanostructured metallic particles exhibiting interesting pharmacological, optoelectronic, tuneable surface plasmon properties and catalytic effects . Metal nanoparticles have attracted much attention in recent times for applications related to chemical sensing, medicine, drug delivery, bioimaging, theranostics , water treatment, antimicrobial, food‐packaging, nonlinear optical devices, catalysis, etc. Such application potential of nanomaterials has spurred interest in novel methods for accessing nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear optics in metal nanoparticles within transparent dielectric media has been studied extensively [1][2][3][4][5][6][7][8][9][10][11][12]. In particular, third order optics using ultrashort (femtosecond) laser pulses in such metal nanoparticle systems have been widely studied and reported.…”
Section: Introductionmentioning
confidence: 99%